Cost models for lot streaming in multistage flow shops with unequal number of sublots between stages. (1st January 2012) - Mokhashi, Khalid Habib; Kim, Seung-Lae
The paper develops a cost model and shows that substantial reduction in the total cost is achieved when unequal number of sublots transfer policy in a multistage flow shop is adopted compared to equal number of sublots transfer policy under the same setting. We conduct sensitivity analysis for the parameters and determine those that account for large percentage reduction in the total cost. We develop another deterministic cost model that includes the purchasing cost and inventory holding cost of the raw material into the first model. This cost model includes a multiple price break all-units discount pricing of raw material.